Surface Properties and Adsorption Capacities of Rice Bran-Activated Carbon - Negara, Dewa Ngakan Ketut Putra; Nindia, Tjokorda Gde Tirta; Septadi, Wayan Nata (Universitas Negeri Malang, 2020)
The growing need for activated carbon requires alternative raw materials to replace non-renewable raw materials whose existence is decreasing. Biomass is a very promising precursor, one of which is from rice bran. This research concerns the development of activated carbon derived from rice bran. Carbonization was carried out at 600 OC and physically activated with nitrogen flow rates of 150 mL/min for 40, 80, and 120 minutes. The activated carbons produced (AC-D40, AC-D80, and AC-D120) were characterized to determine the surface properties, surface morphology, and adsorption capacity for nitrogen and blue methylene adsorptions. The results showed that activated carbon that activated for 80 minutes (AC-D80) had the best characteristics. With a pore surface area of 109.389 m2/g, a pore volume of 0.083 cm3/g, and pores that mostly distributed in the micropore area, this activated carbon has the highest adsorption for nitrogen (53.874 cm3/g) and methylene blue (87.560 mg/g) adsorptions compared to activated carbon with activation times of 40 minutes (AC-D40) and 120 minutes (AC-D120).